Online reputation management with an Electronic word of mouth approach - Maria Advenita Gita Elmada; Maria Vina Elmaresa; Shabriena Wardhani; Wita Adelina Noer Putri (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2022)
Opportunities for managing online reputation for organizations have now begun to be captured by business activists in the communication technology industry in Indonesia. Several corporations from various industries have tried this service to increase their reputation in the digital world, especially on social media. One of the service companies that started to run an online reputation management business and became the subject of this research is Company S, which provides the service of managing reputation in social media. Company S's managing online reputation will be analyzed using three stages of online reputation management: prevention, reaction, and evaluation. This study uses a qualitative approach and the nature of descriptive research, using case study methods, and collecting data using interviews and observations. As a result, Company S has implemented the process of online reputation management in the service they provide. The use of e-WOM, the presence of influencers, the selection of suitable social media, and attractive content planning also affect the online reputation of the clients' organizations.